Breeding report of a new table Phyllanthus emblica cultivar Lütianyougan - LAI Duo; XIAO Weiqiang; QIN Jian; ZHUANG Qingli; PENG Kanghong; SHAO Xuehua (Guoshu xuebao)
Phyllanthus emblica L. is one of important fruit crops with both medicinal and edible values. Currently, fresh variety of P. emblica has high economic benefit and great development potential. Herein, Lütianyougan, a new table variety of P. emblica with excellent traits, was selected from the wild seedling population. In 2013, a native population of P. emblica with different traits was first discovered in Hekou Town, Lühe county, Shanwei City. After many years of field investigation and quality assessment, the fruits from a single plant line was found, which was named as No. 2 tree, whose fruit was bigger than other varieties, and had strong aftertaste and light astringency. Due to its high quality and great potential in the market, No. 2 tree was grafted on wild seedling rootstocks for further field trials in 2014. Through 3 generations of continuous observation on the growth and fruiting habits of grafted seedlings, its offsprings showed stable economic characteristics and high-yield performance with good fruit quality, and its genetic stability was confirmed by inter simple sequence repeat (ISSR) analysis. During 2018—2021, the regional trials were carried out in three different cities including Shanwei, Jieyang and Shantou, and the growth and fruiting habits of No. 2 tree were stable with good performance. In November 2023, it was released as Lütianyougan with the registration code of Yuepingguo 20230009 after the validation by the Guangdong Provincial Crop Variety Examination and Approval Committee. Lütianyougan is a fresh-eating variety of P. emblica. The tree vigor is strong with erect shape. The color of bark is gray-brown, the old branches are offwhite with round-punctiform pores, while the new shoot is slender with dense longitudinal textures. The leaf is imparipinnate, young leaf is yellow-green, and mature leaf is dark green, leathery and rectangular in shape. The flowers are white with six petals. The inflorescence of Lütianyougan is cymes composed of many male flowers and one female flower or all male flowers. The fruit is oblate and smooth with visible ribs, the peel of immature fruit is blueishgreen while the peel of mature fruit is yellowish-green, the pulp is light-green, crisp and slagging, with strong aftertaste, and its astringency is slight. The single fruit mass is 11.0 g, with the maximum of 17.34 g. The fruit shape index is 0.78 and the edible rate is 92.6%. The soluble solid content is 9.44%, the total sugar content is 7.2 g·100 g-1, the titrable acid content is 10.81 g·kg-1, and the vitamin C content is 294.0 mg·100 g-1. In Chaoshan area of Guangdong, the fruit ripens from early October to early November, belonging to the late-maturing variety type. The maturity and fruiting periods are long, and the physiological fruit drop is not obvious. It has large fruit, high yield, good marketability and strong adaptability. Due to high easiness to manage and cultivate, it is suitable for cultivation in Guangdong and similar climate areas.